Impact of the COVID-19 Pandemic on the Effectiveness of a Metabolic Health Telemedicine Intervention for Weight Loss: A Propensity Score Matching Analysis - Athinarayanan, Shaminie J.; Adams, Rebecca N.; VanTieghem, Michelle; McKenzie, Amy L.; Volk, Brittanie M.; Ratner, Robert E.; Phinney, Stephen D. (Frontiers in Public Health, 2022)
COVID-19 pandemic public health measures such as stay-at-home and mandatory work from home orders have been associated with obesogenic lifestyle changes, increased risk of weight gain, and their metabolic sequelae. We sought to assess the impact of this pandemic on weight loss from a telemedicine-delivered very low carbohydrate intervention targeting nutritional ketosis (NKI). Seven hundred forty-six patients with a BMI ≥25kg/m2 enrolled January to March 2020 and treated for at least 1 year with the NKI were classified as the pandemic cohort (PC). A separate cohort of 699 patients who received 1 year of the NKI in the preceding years, enrolled in January to March 2018 were identified as the pre-pandemic cohort (Pre-PC). Demographic and clinical data were obtained from medical records to compare cohorts and assess outcomes. Using propensity score matching, balanced and matched groups of 407 patients in Pre-PC and 407 patients in PC were generated. Longitudinal change in absolute weight and percentage weight change from baseline to 1 year were assessed. Weight significantly decreased in both PC and Pre-PC at 3, 6, 9, and 12 months. The weight loss trajectory was similar in both PC and Pre-PC with no significant weight differences between the two cohorts at 3, 6, 9, and 12 months. On average, the PC lost 7.5% body weight while Pre-PC lost 7.9% over 1 year with no significant difference between the two cohorts (P=0.50) A very low carbohydrate telemedicine intervention delivered comparable and medically significant weight loss independent of pandemic stress and lifestyle limitations.